Factors influencing mercury accumulation in yellow perch (Perca flavescens) and aufwuchs in selected north-central Wisconsin lakes - Cope, William (My University, 1988)
I studied mercury (Hg) accumulation in yellow perch (Perca flavescens) and aufwuchs in 11 lakes with a broad range of pH (5.1 to 7.8) and alkalinity (-12 to 769 ueq/L) in north-central Wisconsin. Mercury uptake was greatest in perch in lakes with alkalinity less than or equal to 40 ueq/L. Multiple regression models, which included combinations of pH, alkalinity, and total Hg concentration and organic content in surficial profundal sediments as independent variables, accounted for 80 to 90% of the variation of Hg burden and concentration in whole yellow perch. Furthermore, preliminary data suggest that Hg concentrations in whole calendar age 2 yellow perch reflect concentrations of the metal in axial muscle tissue of walleyes in north-central Wisconsin lakes. Aufwuchs from artificial substrates accumulated measurable amounts of Hg during 28-d incubation periods; Hg concentrations varied seasonally and were greatest in fall, lowest in spring, and intermediate in summer. Multiple regression models with combinations of five independent variables (pH, alkalinity, total Hg concentration and organic content in surficial profundal sediment, and total watershed area:lake surface area) accounted for 80 to 90% of the variability in Hg concentration and burden (areal) in aufwuchs. When interpretative problems and costs in the use of procedurally defined aufwuchs are considered, the use of a forage fish such as yellow perch seems to be a more efficient approach to monitoring Hg bioavailability. Furthermore, determination of Hg in small yellow perch is a more direct method of assessing potential Hg contamination of gamefish--a topic with human health implications.
Keywords: Mercury -- environmental aspects -- Wisconsin; Lakes -- Microbiology -- Wisconsin; Yellow perch